Feeding rates of raptors during autumn migration in the Central Appalachians 1987–2022 - Verduci, Marzia; Goodrich, Laurie J.; Therrien, Jean-Francois; Ruelas Inzunza, Ernesto (Frontiers in Conservation Science, 2023)
Migratory raptors can fuel their journeys by feeding along the way. To maximize migration success, raptors are suspected to time their movements with the availability of their prey.Feeding rates can vary among species depending on migration distance (long vs. short distance), flight strategies (flapping vs. soaring), and within species according to individual timing (early vs. late migrants). We assessed the feeding rate of four eastern North American migratory raptors over a period of 35 years. Using visual observations collected during autumn migration in the Central Appalachians, we assessed the presence/absence of distended crops of migrants. We quantified the feeding rates of species with different migration ecologies (migration distance, flight strategies), compared within-season (timing) species, and assessed if feeding rates varied over the last 35 years. We found a higher feeding rate in short-distance than in long-distance migrants and in power-flapping vs soaring migrants. We detected a long-term significant increase in feeding rate for most species, more evident in early migratory individuals coupled with a decrease in the feeding rate of late migrants. Understanding how feeding rates vary according to migratory behavior and how the migration ecology of raptors is changing under a scenario of global environmental change is important for their conservation.